1974
DOI: 10.1111/j.1399-3054.1974.tb03118.x
|View full text |Cite
|
Sign up to set email alerts
|

Guaiacyl Lignin Associated with Vessels in Aspen Callus Cultures

Abstract: Lignin from aspen {Populus tremuloides Michx.) tissue cultures containing only mature vessels and undifferentiated parenchymatous cells is exclusively of the guaiacyl type normally associated with gymnosperms. This supports the theory that the guaiacyl and syringyl lignin in angiosperm wood is compartmentalized, with guaiacyl lignin in vessels and syringyl lignin in fibers and ray cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This is consistent with the results of lignin analysis of cultured cells of gymnosperm (Brunow et al 1990(Brunow et al , 1993Fukuda et al 1988; Lange et al 1995) and angiosperm trees (Christiernin et al 2005;Higuchi and Barnoud 1966;Higuchi et al 1960;Wolter et al 1974;Zaprometov et al 1993). Normal developmental or constitutive lignins of gymnosperms and angiosperms are composed of guaiacyl and guaiacyl/ syringyl aromatic rings, respectively, while grass lignins contain significant amounts of p-hydroxyphenyl, as well as guaiacyl and syringyl units (Sarkanen and Hergert 1971).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with the results of lignin analysis of cultured cells of gymnosperm (Brunow et al 1990(Brunow et al , 1993Fukuda et al 1988; Lange et al 1995) and angiosperm trees (Christiernin et al 2005;Higuchi and Barnoud 1966;Higuchi et al 1960;Wolter et al 1974;Zaprometov et al 1993). Normal developmental or constitutive lignins of gymnosperms and angiosperms are composed of guaiacyl and guaiacyl/ syringyl aromatic rings, respectively, while grass lignins contain significant amounts of p-hydroxyphenyl, as well as guaiacyl and syringyl units (Sarkanen and Hergert 1971).…”
Section: Resultssupporting
confidence: 82%
“…In contrast, Higuchi et al (1960) found that a callus culture of the angiosperm tree, Paulownia tomentosa, yielded a lignin composed mainly of guaiacyl units with small amounts of syringyl units, indicating that its OCH 3 content was much lower than that of its corresponding woody tissues, although p-hydroxyphenyl units were not detected. Higuchi et al (1966), Wolter et al (1974), and Christiernin et al (2005) reported similar results for a number of cultured cell lines of angiosperm tree species including Populus tremuloides and Populus tremulaϫtremuloides. In addition, the lignin in Camellia sinensis cells cultured under heterotrophic conditions contained high levels of p-hydroxyphenyl lignin (Zaprometov et al 1993).…”
Section: Resultsmentioning
confidence: 65%
“…Further, the peaks become less distinct due to the absorbance characteristics of p-hydroxy benzoic acid groups occurring in aspen wood distorting the syringyl and guaiacyl spectra. Vessel walls and cell corner regions contain mostly guaiacyl residues (Wolter et al 1974;Musha and Goring 1975;Terashima 2000). This was evidenced by the UV spectra measured in middle lamella regions and vessel walls, which had their maximum at wavelengths of about 276 nm and by immunolabelling showing that these regions contain more condensed G lignin sub-units.…”
Section: Localisation Of Cell Wall Components In 35s-rolc Transgenicsmentioning
confidence: 99%
“…Coniferin turned out to be a much better substrate of these described P-glucosidases as syringin. This might be due to the fact that lignification especially concerned with tracheidal differentiation takes place in chick pea cell cultures essentially as it was observed in aspen cultures [18]. Further work will reveal whether j-glucosidases with preferential specificity for syringin are also detectable.…”
Section: Discussionmentioning
confidence: 99%